تقييم التسرب الحفافي في بعض أنظمة الإلصاق الحديثة - البني رولا (Latakia University Journal -Medical Sciences Series, 2019)
أجريت هذه الدراسة لتقييم درجة التسرب المجهري في حفر الصنف الخامس بتطبيق تقانة الروابط ذاتية التخريش و الروابط منفصلة التخريش ذات العبوات الثلاث, تم استخدام نوعين من المواد الرابطة وهما Etch & prime 3.0 مع الراتنج المركب RBC لشركة (Degussa ) كما استخدم نظام الربط ذو المراحل الثلاث Gluma Solid Bond مع كومبوزت RBC لشركة ( Kulzer ) و طبق كلا النظامين في حالتي رطوبة منطقة التحضير أو جفافها, اعتمدت كل مجموعة على خمسة ضواحك علوية أولى مقلوعة حديثاً لتحري درجة التسرب. لم يكن هنالك فروق دالة بين الحواف الإطباقية و اللثوية لنظام الربط ذاتي التخريش, كان هناك فرق إحصائي الحواف اللثوية و الإطباقية في نظام الربط منفصل التخريش. إن نظام الربط كامل التخريش أفضل من نظام الربط ذاتي التخريش و لا يوجد أهمية تذكر لتقنية الربط الجاف أو الرطب من حيث درجة التسرب. This study was conducted to assess the micro leakage in class 5 restorations, using self-etching adhesive and conventional total-etching three-bottle adhesive systems. Two types of adhesive systems were used: self-etching adhesive Etch and Prime 3.0 with Degufill Mineral resin-based composite RBC (Degussa) and conventional total etching three-bottle Gluma Solid Bond with Flow Line RBC (Kulzer ). The bonding systems were used in the cavities filled with a wet or dry bonding technique. To calculate the degree of leakage, each group consisted of 5 freshly extracted maxillary first premolar teeth. There was a statistical difference in leakage scores between occlusal and gingival margins of the self-etching adhesive bonding system. Using conventional total-etching techniques was better than using self–etching adhesive bonding ones; there was no difference between using wet and dry bonding techniques.